Cadastre 2014 :what lies beyond? - Luo, Xianghuan (2020)
Cadastre 2014 is a unique phenomenon in the land administration domain. Its striking simplicity enables it to speak to policy makers, managers and technicians alike. It enjoys an almost unprecedented role in guiding global land administration discourse, and has done so for almost two decades. In countless countries its impact upon land administration system design is profound. The previous sections of this book reflected on these achievements. Kaufmann and Steudler’s (1998) date of inspiration for Cadastre 2014 arrives. The land administration community pauses for reflection, but also gazes forward. Does Cadastre 2014 remain relevant? What about the decade ahead? Is a new Cadastre 2014 required? What might drive such a vision? What would it include? Answering these questions is no small task: input from the broader disciplines is needed. Here, a humble start is made: each of the above questions is addressed from the viewpoint of the writer. The aim is to kick start a discourse for the post-2014 era: a discussion that should be of interest to land administration researchers and practitioners alike.